(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Ankylosing spondylitis (AS) is a chronic inflammatory autoimmune disease primarily affecting the spine and sacroiliac joints, leading to significant pain, stiffness, and potential disability. The condition, which has a notable male predominance, often presents with severe, persistent inflammatory pain and restricted movement. Current pharmacological therapies include non-steroidal anti-inflammatory drugs (NSAIDs), disease-modifying antirheumatic drugs (DMARDs), and biologics such as TNF inhibitors; however, many patients continue to experience inadequate relief or adverse effects. As a result, there is growing interest in complementary and alternative medicine (CAM), which encompasses various natural healing practices, including traditional herbal treatments and physical therapy. Folk medicine methods, particularly those rooted in traditional practices such as Traditional Chinese Medicine (TCM), offer promising adjunct therapies for managing AS. These approaches often focus on holistic patient care, utilizing natural remedies with fewer side effects compared to conventional medications. Additionally, the integration of non-pharmacological strategies, including supervised exercise programs, plays a critical role in managing symptoms and maintaining functional and physical well-being. Ultimately, ongoing research into the effectiveness of folk medicine methods, particularly within the context of AS management, may provide valuable insights into comprehensive treatment strategies that enhance patient quality of life and reduce reliance on conventional pharmacological therapies.